2019
DOI: 10.1140/epjc/s10052-019-7073-0
|View full text |Cite
|
Sign up to set email alerts
|

Aharonov–Bohm-type effect in the background of a distortion of a vertical line into a vertical spiral

Abstract: It is analysed Aharonov-Bohm-type effects when a spinless quantum particle is in an elastic medium with the distortion of a vertical line into a vertical spiral. By confining the spinless particle to a cylindrical box, the analogue of the Aharonov-Bohm effect for bound states is observed due to influence of the topological defect on the allowed energies of the system. It corresponds to the shift in the angular momentum quantum number yielded by the effects of the topology of the distortion of a vertical line i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
(87 reference statements)
0
21
0
Order By: Relevance
“…It is worth bringing attention to the quantum effects that can rise from a topological defect spacetime with torsion in the framework of rainbow gravity. Recently, one of us has discussed quantum effects in the spacetime with a screw dislocation [42,44,45] and in the spacetime with a spiral dislocation [43]. Therefore, this work raises the possibility of investigating the effects of the rainbow gravity in several scenarios related with the interface between general relativity and relativistic quantum mechanics .…”
Section: Discussionmentioning
confidence: 97%
“…It is worth bringing attention to the quantum effects that can rise from a topological defect spacetime with torsion in the framework of rainbow gravity. Recently, one of us has discussed quantum effects in the spacetime with a screw dislocation [42,44,45] and in the spacetime with a spiral dislocation [43]. Therefore, this work raises the possibility of investigating the effects of the rainbow gravity in several scenarios related with the interface between general relativity and relativistic quantum mechanics .…”
Section: Discussionmentioning
confidence: 97%
“…The energy spectrum of the generalized DKP oscillator rely on the geometric quantum phase, which bring about similar impact from the Aharonov-Bohm effect to the bound states. 70,71…”
Section: Generalized Dkp Oscillator With the Electromagnetic Potentialmentioning
confidence: 99%
“…Here, L is the angular momentum operator and Ω is the constant angular velocity which is taken as Ω = ω ẑ, since we assume the rotating frame along the z-axis. In references [8,9,11,23], it is shown that the presence of the torsion influenced the angular momentum. Particularly, it is noted that the z-component of the angular momentum, Lz = −i∂ ϕ , is being modified by the torsion effect with an additional term.…”
Section: Magnetic Quadrupole Moment Of a Moving Particle In The Prese...mentioning
confidence: 99%
“…Furtado et al considered an external magnetic field and explored the dynamics of the electrons in a medium with the presence of screw dislocation [9]. Da Silva et al considered a non-relativistic particle in an elastic medium and discussed the Aharonov-Bohm-type effects in the background of a distortion of a vertical line into a vertical spiral [11]. Some of the other recent researches that have been carried on can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%